The Influence of Product, Price, Place, and Promotion Marketing Strategies on Skincare Purchase Decisions - Wijaya, Henhen; Amalia, Lia; Anindita, Rina; Rojuaniah, Rojuaniah (Syntax Corporation, 2025)
The beauty industry in Indonesia is rapidly evolving, necessitating effective marketing strategies to comprehend consumer behavior and influence purchase decisions. This study evaluates the impact of product, price, place, and promotion marketing strategies on the purchasing decisions of Skintific brand facial skincare among consumers aged 25 to 55 years. Employing a mixed-methods approach, data were collected via an online questionnaire with a sample of 150 respondents, and the analysis included validity and reliability tests, descriptive statistics, and hypothesis testing using CB SEM. The study found that all marketing strategies positively affect purchase decisions, with product and price being the most influential factors; specifically, product offerings emphasizing quality and variety, combined with competitive pricing, significantly enhance consumer trust and loyalty. These findings underline the importance of adapting marketing strategies to meet consumer expectations in a competitive market, suggesting that skincare brands focus on enhancing product quality and transparency while leveraging effective pricing strategies and distribution channels to optimize consumer engagement and purchase decisions.